Microwave-assisted hydrothermal synthesis of NH4V3O8 microcrystals with controllable morphology - Zakharova, Galina S.; Ottmann, Alexander; Ehrstein, B.; Klingeler, Rüdiger (Materials research bulletin, 2016)
Water-free NH4V3O8 microcrystals have been successfully synthesized by a microwave-assisted hydrothermal synthesis method. The products were characterized by means of X-ray diffraction, scanning electron microscopy, Fourier transform infrared spectroscopy, thermal gravimetric analysis, cyclic voltammetry, and galvanostatic cycling. The results show phase-pure products whose particle size and morphology can be tailored by varying the reaction conditions temperature, time, and initial pH value. For instance, at low pH (2.5⿿3) flower-like agglomerates with primary particles of 20⿿30μm length are found, while at pH 5.5 single microplates with hexagonal outline (30⿿40μm) prevail. The electrochemical studies show reversible lithium de-/intercalation into the layered NH4V3O8 host structures with a maximum initial discharge capacity of 378mAhg⿿1 at 10mAg⿿1. However, there is no clear effect of the materials⿿ morphology on their electrochemical performance.
Gesehen am 01.10.2021
Im Titel sind die Zahlen 4, 3 und 8 tiefgestellt